A construçao da imagem dos mártires nas obras apologeticum e ad martyras de tertuliano: repensando a prática do sacrifício (II-III século d.c.) - OLIVEIRA, Eduardo Soares de (2009)
This study aims to analyze the subject from the sacrifice the issue of martyrdom, and in particular, as the construction and influence. Tertullian, this apologist African city of Carthage, which present as the largest and most influential Christian center in Africa, is presented as a critic and champion of African Christians, from his works Ad Martyras and Apologeticum objectives of this study. African Christianity has greatly developed during the transition period between the II and III century d. C., in Africa Romanized. The works in question are present in the moment of confrontation between the new religion, Christianity, and traditional religious expressions Roman paganism. This confrontation is the persecution of Christians, the latter having a role in the emergence force and expansion of the Christian martyrs during the reign of the Roman Empire in Africa.